Changing attitudes of high school students towards peers with mental health problems - Pejović Milovančević, Milica (Array, 2009)
Stigma refers to the undesirable characteristics linked to mental illness and the adverse cognitive and behavioral consequences. Stigma causes a spiral of alienation and discrimination, leading to social isolation that diminishes chances for recovery. The antistigma program was initiated in schools of Serbia with the aim to address and decrease discrimination of adolescents with mental disorders. The effect of the program on the attitudes of students was evaluated by the Opinion about Mental Illness Questionnaire given to adolescents prior to its implementation and six months afterwards. Social discrimination and the tendency towards social restriction were reduced, while, at the same time, social awareness of mental health-related problems was increased among young people six months after program implementation